2000
DOI: 10.1021/ie000037s
|View full text |Cite
|
Sign up to set email alerts
|

Pellet Breakup Due to Pressure Generated during Wood Pyrolysis

Abstract: A transient unimodel for reacting pellets is considered with various modes of heat and mass transfer and structural changes for wood pyrolysis. Pellet breakup was found to be possible from strength calculations. This leads to an increase in the number of pellets and a decrease in the resistance to heat and mass transfer. The pressure and temperature buildup within 2.7 mm thick pellets was measured for wood pyrolysis/combustion experimentally. The bimodal wood pyrolysis was analyzed, and the rate constant and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…However, when compared with the massive investigations related to physical models, studies on the effects of different devolatilization schemes for biomass fast pyrolysis at the reactor scale are very few. A literature review has shown that the effects of devolatilization schemes on the simulation results were investigated only at the particle scale . The details of biomass fast pyrolysis at the reactor scale are inherently more complicated than those encountered at the particle scale.…”
Section: Introductionmentioning
confidence: 99%
“…However, when compared with the massive investigations related to physical models, studies on the effects of different devolatilization schemes for biomass fast pyrolysis at the reactor scale are very few. A literature review has shown that the effects of devolatilization schemes on the simulation results were investigated only at the particle scale . The details of biomass fast pyrolysis at the reactor scale are inherently more complicated than those encountered at the particle scale.…”
Section: Introductionmentioning
confidence: 99%
“…The governing equations for heat and mass transfer with the boundary and initial conditions and auxiliary equations for some selected properties are given below with with The grain size and porosity are continuously updated using equations presented previously . Heat- and mass-transfer coefficients are obtained through established correlations.…”
Section: Mathematical Equationsmentioning
confidence: 99%
“…Conservation equations for mass and heat transfer The grain size and porosity are continuously updated using equations presented previously. 21 Heat-and masstransfer coefficients are obtained through established correlations.…”
Section: Mathematical Equationsmentioning
confidence: 99%
“…Pressure build-up inside the particle has a significant effect on the product distribution as the trapped gases can undergo secondary reactions . Also, the convective flow of gas out of the particle affects the interaction of the particles with the environment, while high pressure inside the particle can cause mechanical degradation up to the point of cracking of the particle. , …”
Section: Introductionmentioning
confidence: 99%
“…3 Also, the convective flow of gas out of the particle affects the interaction of the particles with the environment, 4 while high pressure inside the particle can cause mechanical degradation up to the point of cracking of the particle. 3,5 Modeling of biomass pyrolysis has received considerable attention in the literature. 6−9 Typically, the models are based on conservation equations for mass and energy, commonly referred to as the balance equations.…”
Section: ■ Introductionmentioning
confidence: 99%